Origins, Worlds, and Life: A Decadal Strategy for Planetary Science and Astrobiology 2023-2032 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The next decade of planetary science and astrobiology holds tremendous promise. New research will expand our understanding of our solar system's origins, how planets form and evolve, under what conditions life can survive, and where to find potentially habitable environments in our solar system and beyond. Origins, Worlds, and Life: A Decadal Strategy for Planetary Science and Astrobiology 2023-2032 highlights key science questions, identifies priority missions, and presents a comprehensive research strategy that includes both planetary defense and human exploration. This report also recommends ways to support the profession as well as the technologies and infrastructure needed to carry out the science.
Keywords: Space and Aeronautics

The National Imperative to Improve Nursing Home Quality: Honoring Our Commitment to Residents, Families, and Staff - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Nursing homes play a unique dual role in the long-term care continuum, serving as a place where people receive needed health care and a place they call home. Ineffective responses to the complex challenges of nursing home care have resulted in a system that often fails to ensure the well-being and safety of nursing home residents. The devastating impact of the COVID-19 pandemic on nursing home residents and staff has renewed attention to the long-standing weaknesses that impede the provision of high-quality nursing home care. With support from a coalition of sponsors, the National Academies of Sciences, Engineering, and Medicine formed the Committee on the Quality of Care in Nursing Homes to examine how the United States delivers, finances, regulates, and measures the quality of nursing home care. The National Imperative to Improve Nursing Home Quality: Honoring Our Commitment to Residents, Families, and Staff identifies seven broad goals and supporting recommendations which provide the overarching framework for a comprehensive approach to improving the quality of care in nursing homes.
Keywords: Health and Medicine

Selected Heritable Disorders of Connective Tissue and Disability - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Heritable disorders of connective tissue (HDCTs) are a diverse group of inherited genetic disorders and subtypes. Because connective tissue is found throughout the body, the impairments associated with HDCTs manifest in multiple body systems and may change or vary in severity throughout an affected individual's lifetime. In some cases, these impairments may be severe enough to qualify an eligible child or adult for monetary benefits through the U.S. Social Security Administration's (SSA's) Social Security Disability Insurance or Supplemental Security Income program. SSA asked the National Academies of Sciences, Engineering, and Medicine to convene an expert committee that would provide current information regarding the diagnosis, treatment, and prognosis of selected HDCTs, including Marfan syndrome and the Ehlers-Danlos syndromes, and the effect of the disorders and their treatment on functioning. The resulting report, Selected Heritable Disorders of Connective Tissue and Disability, presents the committee's findings and conclusions.
Keywords: Health and Medicine

Improving Representation in Clinical Trials and Research: Building Research Equity for Women and Underrepresented Groups - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
The United States has long made substantial investments in clinical research with the goal of improving the health and well-being of our nation. There is no doubt that these investments have contributed significantly to treating and preventing disease and extending human life. Nevertheless, clinical research faces a critical shortcoming. Currently, large swaths of the U.S. population, and those that often face the greatest health challenges, are less able to benefit from these discoveries because they are not adequately represented in clinical research studies. While progress has been made with representation of white women in clinical trials and clinical research, there has been little progress in the last three decades to increase participation of racial and ethnic minority population groups. This underrepresentation is compounding health disparities, with serious consequences for underrepresented groups and for the nation. At the request of Congress, Improving Representation in Clinical Trials and Research: Building Research Equity for Women and Underrepresented Groups identifies policies, procedures, programs, or projects aimed at increasing the inclusion of these groups in clinical research and the specific strategies used by those conducting clinical trials and clinical and translational research to improve diversity and inclusion. This report models the potential economic benefits of full inclusion of men, women, and racial and ethnic groups in clinical research and highlights new programs and interventions in medical centers and other clinical settings designed to increase participation.
Keywords: Policy for Science and Technology

Traumatic Brain Injury: A Roadmap for Accelerating Progress - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Every community is affected by traumatic brain injury (TBI). Causes as diverse as falls, sports injuries, vehicle collisions, domestic violence, and military incidents can result in injuries across a spectrum of severity and age groups. Just as the many causes of TBI and the people who experience it are diverse, so too are the physiological, cognitive, and behavioral changes that can occur following injury. The overall TBI ecosystem is not limited to healthcare and research, but includes the related systems that administer and finance healthcare, accredit care facilities, and provide regulatory approval and oversight of products and therapies. TBI also intersects with the wide range of community organizations and institutions in which people return to learning, work, and play, including the education system, work environments, professional and amateur sports associations, the criminal justice system, and others. Traumatic Brain Injury: A Roadmap for Accelerating Progress examines the current landscape of basic, translational, and clinical TBI research and identifies gaps and opportunities to accelerate research progress and improve care with a focus on the biological, psychological, sociological, and ecological impacts. This report calls not merely for improvement, but for a transformation of attitudes, understanding, investments, and care systems for TBI.
Keywords: Health and Medicine

Realizing the Promise of Equity in the Organ Transplantation System - Kenneth W. Kizer; Rebecca A. English; Meredith Hackmann (The National Academies Press, 2022)
Each year, the individuals and organizations in the U.S. organ donation, procurement, allocation, and distribution system work together to provide transplants to many thousands of people, but thousands more die before getting a transplant due to the ongoing shortage of deceased donor organs and inequitable access to transplant waiting lists. Realizing the Promise of Equity in the Organ Transplantation System, a new consensus study report from the National Academies of Sciences, Engineering, and Medicine’s Committee on A Fairer and More Equitable, Cost-Effective, and Transparent System of Donor Organ Procurement, Allocation, and Distribution, provides expert recommendations to improve fairness, equity, transparency, and cost-effectiveness in the donor organ system.
Keywords: Health and Medicine

Measuring Sex, Gender Identity, and Sexual Orientation - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Sex, gender identity, and sexual orientation are key indicators of the demographic diversity in the United States. Sex and gender are often conflated under the assumptions that they are mutually determined and do not differ from each other; however, the growing visibility of transgender and intersex populations, as well as efforts to improve the measurement of sex and gender across many scientific fields, has demonstrated the need to reconsider how sex, gender, and the relationship between them are conceptualized. This is turn affects sexual orientation, because it is defined on the basis of the relationship between a person's own sex or gender and that of their actual or preferred partners. Sex, gender, and sexual orientation are core aspects of identity that shape opportunities, experiences with discrimination, and outcomes through the life course; therefore, it is crucial that measures of these concepts accurately capture their complexity. Recognition of the diversity within the lesbian, gay, bisexual, transgender, queer, intersex, and other sexual and gender minorities - the LGBTQI+ population - has also led to a reexamination of how the concepts of sex, gender identity, and sexual orientation are measured. Better measurement will improve the ability to identify sexual and gender minority populations and understand the challenges they face. LGBTQI+ people continue to experience disparate and inequitable treatment, including harassment, discrimination, and violence, which in turn affects outcomes in many areas of everyday life, including health and access to health care services, economic and educational attainment, and family and social support. Though knowledge of these disparities has increased significantly over the past decade, glaring gaps remain, often driven by a lack of reliable data. Measuring Sex, Gender Identity, and Sexual Orientation recommends that the National Institutes of Health (NIH) adopt new practices for collecting data on sex, gender, and sexual orientation - including collecting gender data by default, and not conflating gender with sex as a biological variable. The report recommends standardized language to be used in survey questions that ask about a respondent's sex, gender identity, and sexual orientation. Better measurements will improve data quality, as well as the NIH's ability to identify LGBTQI+ populations and understand the challenges they face.
Keywords: Behavioral and Social Sciences

Global Roadmap for Healthy Longevity - National Academy of Medicine (The National Academies Press, 2022)
With unprecedented global aging, societies must undertake all-of-society efforts to maximize the benefits and minimize the burdens of aging populations. The Global Roadmap for Healthy Longevity (Global Roadmap) describes a realistic vision of healthy longevity that could be achieved by 2050. The vision includes full inclusion of people of all ages, regardless of health or functional status, in all aspects of society and societies characterized by social cohesion and equity. To achieve the vision, Global Roadmap recommends changes that need to be made to health systems, social infrastructure, physical environments, education, work, and retirement. In some cases, the recommended changes benefit older people most directly, but when older people thrive, people of all ages benefit. If taken up, the recommendations of this report can support individuals of all ages in all corners of the globe to live long, meaningful, and purpose-driven lives by 2050.
Keywords: Health and Medicine

Guidance on PFAS Exposure, Testing, and Clinical Follow-Up - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
In thousands of communities across the United States, drinking water is contaminated with chemicals known as perfluoroalkyl and polyfluoroalkyl substances (PFAS). PFAS are used in a wide range of products, such as non-stick cookware, water and stain repellent fabrics, and fire-fighting foam, because they have properties that repel oil and water, reduce friction, and resist temperature changes. PFAS can leak into the environment where they are made, used, disposed of, or spilled. PFAS exposure has been linked to a number of adverse health effects including certain cancers, thyroid dysfunction, changes in cholesterol, and small reductions in birth weight. This report recommends that the Centers for Disease Control and Prevention (CDC) update its clinical guidance to advise clinicians to offer PFAS blood testing to patients who are likely to have a history of elevated exposure, such as those with occupational exposures or those who live in areas known to be contaminated. If testing reveals PFAS levels associated with an increased risk of adverse effects, patients should receive regular screenings and monitoring for these and other health impacts. Guidance on PFAS Exposure, Testing, and Clinical Follow-Up recommends that the CDC, Agency for Toxic Substances and Disease Registry (ATSDR), and public health departments support clinicians by creating educational materials on PFAS exposure, potential health effects, the limitations of testing, and the benefits and harms of testing.
Keywords: Environment and Environmental Studies; Health and Medicine

New Directions for Chemical Engineering - National Academy of Engineering; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Over the past century, the work of chemical engineers has helped transform societies and the lives of individuals, from the synthetic fertilizers that helped feed the world to the development of novel materials used in fuels, electronics, medical devices, and other products. Chemical engineers' ability to apply systems-level thinking from molecular to manufacturing scales uniquely positions them to address today’s most pressing problems, including climate change and the overuse of resources by a growing population. New Directions for Chemical Engineering details a vision to guide chemical engineering research, innovation, and education over the next few decades. This report calls for new investments in U.S. chemical engineering and the interdisciplinary, cross-sector collaborations necessary to advance the societal goals of transitioning to a low-carbon energy system, ensuring our production and use of food and water is sustainable, developing medical advances and engineering solutions to health equity, and manufacturing with less waste and pollution. The report also calls for changes in chemical engineering education to ensure the next generation of chemical engineers is more diverse and equipped with the skills necessary to address the challenges ahead.
Keywords: Engineering and Technology

Biodiversity at Risk: Today's Choices Matter - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
A growing body of evidence has sounded the alarm that the biodiversity that supports and sustains life on Earth is at risk. Habitat destruction, resource exploitation, and climate change are among the many stressors that have put 1 million species under threat of extinction and sharply reduced the populations of many plant and animal species. While researchers and global leaders ramp up efforts to address this existential threat, the significance of species loss and the value of preserving biodiversity is not widely recognized by policy makers or the public. This booklet, produced by an international committee of experts, provides a publicly accessible overview of the many dimensions of biodiversity and why it's vital to the health of all life on the planet. The booklet also examines the causes of biodiversity loss and presents actions that can be taken from the individual to the global level to stop this decline.
Keywords: Biology and Life Sciences

Physics of Life - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Biological physics, or the physics of living systems, has emerged fully as a field of physics, alongside more traditional fields of astrophysics and cosmology, atomic, molecular and optical physics, condensed matter physics, nuclear physics, particle physics, and plasma physics. This new field brings the physicist's style of inquiry to bear on the beautiful phenomena of life. The enormous range of phenomena encountered in living systems - phenomena that often have no analog or precedent in the inanimate world - means that the intellectual agenda of biological physics is exceptionally broad, even by the ambitious standards of physics. Physics of Life is the first decadal survey of this field, as part of a broader decadal survey of physics. This report communicates the importance of biological physics research; addresses what must be done to realize the promise of this new field; and provides guidance for informed decisions about funding, workforce, and research directions.
Keywords: Math, Chemistry, and Physics; Biology and Life Sciences

Why Indoor Chemistry Matters - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
People spend the vast majority of their time inside their homes and other indoor environments where they are exposed to a wide range of chemicals from building materials, furnishings, occupants, cooking, consumer products, and other sources. Despite research to date, very little is known about how exposures to indoor chemicals across complex chemical phases and pathways affect human health. The COVID-19 pandemic has only increased public awareness of indoor environments and shed light on the many outstanding questions about how best to manage chemicals indoors. This report identifies gaps in current research and understanding of indoor chemistry and new approaches that can be applied to measure, manage, and limit chemical exposures. Why Indoor Chemistry Matters calls for further research about the chemical transformations that can occur indoors, pathways and timing of indoor chemical exposure, and the cumulative and long-term impacts of exposure on human health. Research priorities should consider factors that contribute to measurable environmental health disparities that affect vulnerable populations, such as the age, location, and condition of buildings that can alter exposures to indoor chemicals.
Keywords: Math, Chemistry, and Physics; Environment and Environmental Studies

The Future of Education Research at IES: Advancing an Equity-Oriented Science - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
In 2002 Congress passed the Education Sciences Reform Act of 2002 (ESRA), authorizing the creation of the Institute of Education Sciences (IES) as the research, evaluation, statistics, and assessment arm of the Department of Education, and crystallizing the federal government's commitment to providing national leadership in expanding fundamental knowledge and understanding of education from early childhood through postsecondary study. IES shares information on the condition and progress of education in the United States, including early childhood education and special education; educational practices that support learning and improve academic achievement and access to educational opportunities for all students; and the effectiveness of federal and other education programs. In response to a request from the Institute of Education Sciences, this report provides guidance on the future of education research at the National Center for Education Research and the National Center for Special Education Research, two centers directed by IES. This report identifies critical problems and issues, new methods and approaches, and new and different kinds of research training investments.
Keywords: Education

Human-AI Teaming: State-of-the-Art and Research Needs - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Although artificial intelligence (AI) has many potential benefits, it has also been shown to suffer from a number of challenges for successful performance in complex real-world environments such as military operations, including brittleness, perceptual limitations, hidden biases, and lack of a model of causation important for understanding and predicting future events. These limitations mean that AI will remain inadequate for operating on its own in many complex and novel situations for the foreseeable future, and that AI will need to be carefully managed by humans to achieve their desired utility. Human-AI Teaming: State-of-the-Art and Research Needs examines the factors that are relevant to the design and implementation of AI systems with respect to human operations. This report provides an overview of the state of research on human-AI teaming to determine gaps and future research priorities and explores critical human-systems integration issues for achieving optimal performance.
Keywords: Behavioral and Social Sciences